Roles of Neuropeptide Y in Neurodegenerative and Neuroimmune Diseases - Li, Chunrong; Wu, Xiujuan; Liu, Shan; Zhao, Yue; Zhu, Jie; Liu, Kangding (Frontiers in Neuroscience, 2019)
Neuropeptide Y (NPY) is a neurotransmitter or neuromodulator that mainly exists in the nervous system. It plays a neuroprotective role in organisms and widely participates in the regulation of various physiological processes in vivo. Studies in both humans and animal models have been revealed that NPY levels are altered in some neurodegenerative and neuroimmune disorders. NPY plays various roles in these diseases, such as exerting a neuroprotective effect, increasing trophic support, decreasing excitotoxicity, regulating calcium homeostasis, and attenuating neuroinflammation. In this review, we will focus on the roles of NPY in the pathological mechanisms of neurodegenerative and neuroimmune diseases, highlighting NPY as a potential therapeutic target in these diseases.